A Comparative Study of the Solubility and Sorption Properties of Resin Modified Glass Ionomer and a Bioactive Liner - H Heshmat; M hoorizad ganjkar; N Sanaei; SF Tabatabaei; MJ Kharazifard (Islamic Azad University, 2022)
Background and Aim: This study aimed to compare the sorption and solubility properties of ACTIVA BioACTIVE liner and resin modified glass ionomer (RMGI).   Materials and Methods: In this in vitro study, a total of 30 samples were fabricated from each liner measuring 15 mm in diameter and 1 mm in thickness according to ISO 2009:4049. They were then divided into 6 subgroups (n=5) to assess their water solubility after 1 week and 8 weeks, water sorption after 1 week and 8 weeks, and acid solubility after 1 week and 8 weeks. The samples were then weighed, and placed in vials containing artificial saliva or lactic acid and incubated at 37°C for 1 week or 8 weeks according to specimen grouping. Afterwards, each specimen was weighed again. Sorption and solubility were calculated according to difference in weight of the samples. Data were analyzed by two-way ANOVA(alpha=0.05). Results: RMGI showed greater water solubility and sorption compared with ACTIVA BioACTIVE liner after 1 week of storage (P=0.00). No significant difference was found in water solubility (P=0.64) and sorption (P=0.15) after 8 weeks of storage. There was no significant difference in acid solubility of RMGI and ACTIVA BioACTIVE liner after 1 week (P=0.30) or 8 weeks of storage (P=0.60) Conclusion: Water sorption and solubility of RMGI were greater than those of ACTIVA BioACTIVE within the first week after setting but they were similar in long-term assessment. RMGI and ACTIVA BioACTIVE were not different in terms of acid resistance.